2005
DOI: 10.1111/j.1600-0781.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

UVA1 phototherapy for disseminated granuloma annulare

Abstract: UVA1 phototherapy provided good or excellent results in half of our 20 patients with disseminated granuloma annulare. In the majority of patients with a satisfactory response, however, discontinuation of treatment was followed by early recurrence of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Small studies using UV-A1 have shown improvement in lesions; however, relapses were common after discontinuation of therapy. [103][104][105] Psoralen-UV-A (PUVA) has been effective in clearing the lesions of GA in case reports and small case series. [106][107][108][109] As in the case of UV-A1 therapy, although many patients showed improvement, [106][107][108][109] recurrence was common and maintenance therapy was required.…”
Section: Evaluation and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Small studies using UV-A1 have shown improvement in lesions; however, relapses were common after discontinuation of therapy. [103][104][105] Psoralen-UV-A (PUVA) has been effective in clearing the lesions of GA in case reports and small case series. [106][107][108][109] As in the case of UV-A1 therapy, although many patients showed improvement, [106][107][108][109] recurrence was common and maintenance therapy was required.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…Immunosuppression with methotrexate, cyclosporine, and TNF-a inhibitors can be considered in patients with severe disease that has been recalcitrant to other therapies. 28,[87][88][89][90][91][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][114][115][116][117][118][119][120][121][122][123][124]126,127,129,130,[132][133][134][140][141][142][144][145][146][147][148]150,…”
Section: Evaluation and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, as oral PUVA and bath-PUVA only partially suppress disease activity, chemophototherapy should be reserved for severe and recalcitrant cases, especially as the cumulative dosage has to be limited due to its carcinogenic potential. Comparable results were achieved in a study including 20 patients treated with UVA1: in 50% of the patients lesions cleared or at least markedly improved, but in the follow-up 7 of the 9 responders relapsed within an average time span of 3 months [36]. …”
Section: Discussionmentioning
confidence: 68%
“…These cases clearly represent a major therapeutic challenge and many patients remain troubled by the appearance. The visible and unsightly nature of this skin condition has led to the proposal of a variety of topical and/or systemic treatment methods [5][6][7][8][9][10][11][12][13][14][15] (Table 1)-all with varying degrees of success and each with its own treatment-associated morbidity.…”
Section: Introductionmentioning
confidence: 99%